2010
DOI: 10.15288/jsad.2010.71.78
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Intimate Partner Violence Perpetration Among College Students: The Role of Self-Determination

Abstract: ABSTRACT. Objective:The present research examined the role of self-determination theory in alcohol consumption and intimate partner violence (IPV) perpetration among college students. We were interested in evaluating the extent to which individual differences in self-determination (i.e., autonomous and controlled orientations) may infl uence problematic alcohol use and male-to-female IPV perpetration and the extent to which problem drinking may mediate the associations between self-determination and IPV perpet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 56 publications
(58 reference statements)
5
30
0
1
Order By: Relevance
“…A number of cross-sectional studies have shown that alcohol problems are related to perpetration (Baker & Stith, 2008; Fossos, Neighbors, Kaysen, & Hove, 2007; Hove, Parkhill, Neighbors, McConchie, & Fossos, 2010), and perpetrators have more alcohol problems than non-perpetrators (Cogan & Ballinger, 2006; Lundeberg, Stith, Penn, & Ward, 2004). Alcohol problems refer to problems that occur as a result of alcohol use, such as drinking and driving, arguments, etc.…”
Section: Dating Violence and Substance Usementioning
confidence: 99%
“…A number of cross-sectional studies have shown that alcohol problems are related to perpetration (Baker & Stith, 2008; Fossos, Neighbors, Kaysen, & Hove, 2007; Hove, Parkhill, Neighbors, McConchie, & Fossos, 2010), and perpetrators have more alcohol problems than non-perpetrators (Cogan & Ballinger, 2006; Lundeberg, Stith, Penn, & Ward, 2004). Alcohol problems refer to problems that occur as a result of alcohol use, such as drinking and driving, arguments, etc.…”
Section: Dating Violence and Substance Usementioning
confidence: 99%
“…Langenderfer (2013) carried out a meta-analysis with 8 studies on intimate partner violence and use of alcohol, concluding that rates of perpetration of violent acts by men on their partners ranged from 4% to 78.1% (Cunradi, 2009;Hove, Parkhill, Neighbors, McConchie, & Fossos, 2010;Lipsky & Caetano, 2011;McKinney, Caetano, Ramisetty-Mikler, & Nelson, 2009;Rhodes et al, 2009;Taft, Schumm, Orazem, Meis, & Pinto, 2010), while of those men who reported having been violent towards their partners, between 9% and 59.7% reported having got drunk (5 or more alcoholic drinks) (Cunradi, 2009;Lipsky & Caetano, 2011;McKinney et al, 2009), and between and 17.8% and 50% said they had sometimes drunk excessively (Lipsky & Caetano, 2011;Rhodes et al, 2009). Finally, Langenderfer (2013 points out that alcohol problems correlate to a statistically significant degree with intimate partner violence (Hove et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since gaining external approval can be difficult to maintain but easy to lose, controlled individuals exert an exorbitant amount of effort in regulating their behaviors; but ironically, feel less in control of their overall fate, because their decisions have been heavily influenced by external factors. Thus, controlled orientation has been linked to such negative consequences as higher levels of stress (Deci & Ryan, 1985a); increased aggression (Deci & Ryan, 1985b); and committing acts of violence against an intimate partner (Hove, Parkhill, Neighbors, McConchie, & Foss, 2010). …”
Section: Introductionmentioning
confidence: 99%